Синхронізація генераторів на ЛПД імпульсної та безперервної дії у мм-діапазоні довжини хвиль. Частина 1. Конструкції генераторів і узагальнена модель їх синхронізації зовнішнім сигналом - Karushkin, Mykola (PE "Politekhperiodika", Book and Journal Publishers, 2021)
Advances in the development of ultrahigh-frequency semiconductor electronics open wide opportunities for developing optimal schemes and designs of microwave power sources in the millimeter wavelength range providing high stability of the frequency and electromagnetic oscillation phase. Synchronized diode generators used in transmit/receive module for active phased array antennas, coherent low-power radar stations, etc. show great promise. The mode of external synchronization of semiconductor generators allows effectively implementing the task of creating output stages of the transmitters with high gain factor, low frequency noise and an output power level corresponding to the maximum power mode.This article presents the first of two parts of the study, which summarizes the results achieved so far in the development of synchronized oscillators based on impact ionization avalanche transit-time (IMPATT) diodes. The first part presents the electrodynamic designs of the oscillators, which are synchronized with an external source of microwave oscillations and contain a resonant oscillating system with a silicon IMPATT diode. The silicon two-drift IMPATT diode was chosen as an active element due to the fact that its use allows reaching significant levels of pulsed microwave power – an order of magnitude higher than those of the most well-known HEMT and pHEMT transistors in the millimeter wavelength range. It is shown that to reduce losses, the oscillating system should be made in the form of a radial resonator with a diode casing, which has distributed parameters. This eliminates the use of additional reactive inhomogeneities in the initial cross-section of the waveguide section of the generator. Due to the low quality factor of the resonant casing of the diode, the generalized quality factor of the microwave circuit takes the minimum value required to implement a stable generator synchronization process in the millimeter wavelength range. The second part of the work will be devoted to synchronized pulse generators with an output power of 20–150 W.